Genetic Polymorphisms of 30 InDel Loci in Ewenki Ethnic Group from Inner Mongolia - JIN XIAO-YE; WEI YUAN-YUAN; HE YONG-FENG (Editorial Office of Journal of Forensic Medicine, 2017)
Objective To study the genetic polymorphisms of 30 insertion/deletion （InDel） loci and evaluate their forensic application in Ewenki ethnic group from Inner Mongolia. Methods Peripheral blood samples were collected from 87 unrelated healthy individuals in Ewenki ethnic group. Genomic DNA were extracted, and 30 InDel loci of the samples were multiplex amplified and genotyped. Hardy-Weinberg balance tests were preformed for all loci and genetic parameters were calculated by modified PowerStats v1.2 software. The linkage disequilibrium between loci were tested by SNPAnalyzer v2.0 software. Based on the allele frequencies of 30 InDel loci, the genetic relationships between Ewenki ethnic group and other populations were evaluated by analysis of molecular variance, principal component analysis and phylogenetic reconstruction. Results After correction, 30 InDel loci conformed to Hardy-Weinberg equilibrium. It was found that the pairwise InDel loci were in linkage equilibrium after Bonferroni correction. The results of population genetics indicated that Ewenki ethnic group had close genetic relationships with Henan Han and Beijing Han populations; whereas it was significantly different from several populations in Europe and Mexico. Conclusion There are relatively high genetic polymorphisms on 30 InDel loci of Ewenki ethnic group from Inner Mongolia, which can be used as a helpful supplement application for STR detection system.